2016
DOI: 10.4314/sajas.v46i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various pre-slaughter conditions on pig carcasses and meat quality in a low-input slaughter facility

Abstract: The aim of this study was to determine the effects of gender, slaughter weight, stocking density, lairage time and season on carcass and meat quality parameters in a low-input production system. The study was conducted on 400 slaughter pigs (200 barrows and 200 gilts) with live weight of 115.0 ± 4.70 kg. Barrows had higher slaughter and carcass weights, fat thickness and lower meatiness. Heavier pigs had higher hot and cold carcass weights, fat thickness, lower meatiness, and higher incidences of pale, soft an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
2
21
0
5
Order By: Relevance
“…As mentioned before, more than a third of the examined slaughter pigs (31.25%) had fighting-type bruises on their carcasses, probably as a consequence of aggressive behavior caused by adverse weather conditions on the day of slaughter. During this investigation, pigs slaughtered in summer and winter were exposed to extreme weather conditions, such as high relative humidity (76.2-84.5%) and environmental temperatures above (29.5 to 35.0 • C) or below (−9.5 to −5.5 • C) the thermoneutral zone for slaughter weight pigs (15-25 • C, [4]). When the environmental temperature exceeds the upper threshold of thermal tolerance, the resting time is interrupted and pigs start to search for cool areas to lie down without contact with other individuals [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned before, more than a third of the examined slaughter pigs (31.25%) had fighting-type bruises on their carcasses, probably as a consequence of aggressive behavior caused by adverse weather conditions on the day of slaughter. During this investigation, pigs slaughtered in summer and winter were exposed to extreme weather conditions, such as high relative humidity (76.2-84.5%) and environmental temperatures above (29.5 to 35.0 • C) or below (−9.5 to −5.5 • C) the thermoneutral zone for slaughter weight pigs (15-25 • C, [4]). When the environmental temperature exceeds the upper threshold of thermal tolerance, the resting time is interrupted and pigs start to search for cool areas to lie down without contact with other individuals [46].…”
Section: Discussionmentioning
confidence: 99%
“…If this is not possible, pigs become agitated, which increases aggression between pen-mates [46]. When the environmental temperature falls below the lower threshold of thermal tolerance, pigs tend to maintain body temperature by lying in close proximity to each other to create a warmer microclimate [4,45]. However, grouping of pigs decreases the space allocation, which increases fights between pen-mates trying to find a place to rest [4,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of Ascaris suum infection and liver milk spots can lead to the following negative effects: (1) farm economic losses attributed to decreased daily weight gain, anthelmintic treatment costs, depressed growth rates and feed conversion efficiency (Sanchez-Vazquez et al, 2010), (2) changes in hematological values (Makinde et al, 1996;Zanga et al, 2003;Wieczorek et al, 2006), (3) slaughterhouse operator losses due to trimmings and disposal of organs unsuitable for human consumption (Pyz-Lukasik and Prost, 1999), (4) lower carcass and pork quality (Theodoropoulos et al, 2004;Knecht et al, 2011Knecht et al, , 2012. A number of studies revealed that pork quality is affected by many different factors, such as feeding, slaughter weight and gender, pre-slaughter and slaughter conditions (Šefer et al, 2015;Rocha et al, 2016;Đorđević et al, 2016;Čobanović et al, 2016b, 2016c. However, only one published article is available in the literature about the relationship between liver milk spots and pork quality (Theodoropoulos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%